The impact of CwlM depletion on the susceptibility of Mycobacterium smegmatis to anti-tuberculosis drugs - Shufeng Yang; Yuzhao Ren; Yu Wu; Xinyang Li; Xin Liu; Guoying Deng (PLoS ONE, 2025)
CwlM, identified as an N-acetylmuramoyl-l-alanine amidase, plays crucial roles in the synthesis and remodeling of peptidoglycan in mycobacteria. This protein also appears to participate in both drug susceptibility and tolerance mechanisms within these organisms. In our study, we employed CRISPR interference (CRISPRi) to deplete CwlM in Mycobacterium smegmatis ( M. smegmatis ) and examined the resulting effects on the susceptibility of mycobacteria to first-line anti-tuberculosis drugs, including isoniazid (INH), rifampicin (RIF), pyrazinamide (PZA), and ethambutol (EMB), as well as the β-lactams cefoxitin and imipenem. Our findings revealed that CwlM depletion increased the susceptibility of the bacterium to RIF, EMB, cefoxitin, and imipenem, while tolerance was heightened against INH and PZA. The enhanced antibiotic susceptibility can primarily be attributed to increased permeability of the bacterial cell wall. Conversely, the observed tolerance to INH might be ascribed to elevated expression of the amidase known as hydrazidase along with its LuxR-type regulator. Furthermore, several genes associated with peptidoglycan synthesis appeared to correlate with increased expression levels of either hydrazidase or its LuxR-type regulator. Collectively, these findings indicate that CwlM depletion significantly influences the susceptibility of M. smegmatis towards certain anti-tuberculosis drugs and may be implicated in drug susceptibility and tolerance mechanisms in M. smegmatis .